Deep soil contributions to global nitrogen budgets - Maya Almaraz; Chao Wang; Michelle Y. Wong (Nature Communications)
Abstract Previous estimates of deep soil inorganic nitrogen (N) reservoirs have been mainly limited to desert soils, however, recent evidence suggests that deep soil pools are far more ubiquitous across biomes and therefore may be important for global N budgets. Here, we used observations from 280 deep soil profiles (2-205 m) across a wide array of ecosystem and land cover types to seek insight into the full geospatial variation of deep soil nitrate. Using a random forest machine learning approach we estimate a total deep soil nitrate pool of 15.2 ( ± 1.1 SD) Pg of N. When included in the global soil N pool, our estimates of deep soil N increase the global N storage budget by 16%. Estimating these deep soil N pools continues to add to our understanding of soils as a fate for anthropogenically fixed N, and the critical role that deep soils play in our biosphere.